What will studies of Fulani individuals naturally exposed to malaria teach us about protective immunity to malaria? - Troye-Blomberg, Marita; Arama, Charles; Quin, Jaclyn; Bujila, Ioana; Östlund Farrants, Ann-Kristin (Scandinavian journal of immunology, 2020)
There are an estimated over 200 million yearly cases of malaria worldwide. Despite concerted international effort to combat the disease, it still causes approximately half a million deaths every year, the majority of which are young children with Plasmodium falciparum infection in sub-Saharan Africa. Successes are largely attributed to malaria prevention strategies, such as insecticide-treated mosquito nets and indoor spraying, as well as improved access to existing treatments. One important hurdle to new approaches for the treatment and prevention of malaria is our limited understanding of the biology of Plasmodium infection and its complex interaction with the immune system of its human host. Therefore, the elimination of malaria in Africa not only relies on existing tools to reduce malaria burden, but also requires fundamental research to develop innovative approaches. Here, we summarize our discoveries from investigations of ethnic groups of West Africa who have different susceptibility to malaria.
Keywords: lidé; Malaria, Falciparum; Humans; tropická malárie; Africa South of the Sahara; subsaharská Afrika